Access to Spatial Data: The Political Power of Legal Control Mechanisms - (:unkn) unknown (My University, 2012)
According to the U.S. Supreme Court (Island Trees School District v. Pico, 457 U.S. 853, 1982), the Constitution presupposes that the free flow of information between the government and the public is essential to maintaining an informed citizenry, which in turn is essential to holding governments accountable. However, local governments are increasingly using various legal mechanisms to limit public access to geographic information (GI), and this in turn can potentially disrupt this balance. Licensing and copyright are two such mechanisms that local government agencies are using to limit GI access and distribution. If information is power, whoever controls information, controls power. Therefore those who influence the political and legal processes that control access to geographic information control power. By using the theoretical frameworks of GIS and Society, Legal and Policy Analysis, Politics of Scale and Neoliberalism, a truly multidisciplinary investigation, new theories of the political nature of knowledge access may be developed. This dissertation is composed of three papers. The first paper examines the growth and development of land records modernization in Wisconsin, and through the lenses of the Critical GIS and political economy, contributes to the body of knowledge within Critical GIS by examining one of the United State's first successful forays into modernizing land records. The paper documents the socially constructed relationship between technology and geography. This historic examination of how one state successfully built a program through years of cooperation and conflicts among powerful actors and networks, at and between scales, during times of plentiful and lean government resources provides insights into issues that still plague data cooperation between groups with different agendas today. The second and third papers focus on the legal and political processes that frame access to geographic information in Wisconsin and California. Through an examination of court cases in California and Wisconsin and the laws that impact GI access, suggested public policy to increase access to this government produced information is suggested. This research will contribute to both the GIS and Society and Legal and Policy analysis literature by documenting the legal and political impacts of GI data sharing.
Keywords: Access; Geographic Information; Law; Policy Analysis; Power; Wisconsin Land Information Program